A method for modifying basalt fiber, modified basalt fiber and application thereof
The modified basalt fibers with porous structures are formed through ball milling and hydrothermal reaction, which solves the problems of low fiber formation efficiency and difficulty in uniform dispersion of basalt fibers in the prior art, and significantly improves the durability and anti-aging properties of asphalt materials.
Patent Information
- Application Number
- CN202410049393.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-01-12
AI Technical Summary
The existing basalt fiber preparation methods have low fiber-forming efficiency and are difficult to disperse uniformly in asphalt materials, resulting in poor durability of asphalt materials and susceptible to rainwater to layer, and cannot effectively improve performance.
The basalt particles after screening and the oxide particles were mixed with the ball mill, melted and brushed, and then zinc oxide was formed in the hydrothermal reaction using zinc salt, cetyltrimethylammonium bromide, sodium hydroxide and ethylenediamine in the hydrothermal reaction. The precursor solution is coated with nano zinc oxide to form modified basalt fibers with porous structures.
It improves the combination effect of basalt fibers and asphalt materials, enhances the anti-ultraviolet aging properties and surface adhesion of asphalt, and extends the service life of asphalt materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of basalt fibers, and in particular to a basalt fiber modification method, modified basalt fibers and applications thereof. Background Art
[0002] Asphalt is one of the most widely used road construction materials. It is mainly composed of hydrocarbons and their derivatives, and has certain plasticity, viscoelasticity, and shock and noise reduction properties. However, in actual use, asphalt is prone to softening at high temperatures and cracking at low temperatures, especially due to its poor temperature sensitivity. This results in poor durability of asphalt.
[0003] In order to solve the above technical problems, researchers in this field have proposed to modify the asphalt material by introducing a modifier to improve the durability of the asphalt material, such as using a modifier such as basalt fiber for improvement.
[0004] However, the basalt fiber prepared by the prior art is mainly prepared by directly melting the basalt raw material at high temperature and then drawing it at high speed through a platinum-rhodium alloy drawing plate. However, this method has low fiber-forming efficiency, and it is difficult to evenly disperse the obtained basalt fiber in the asphalt material within tens of seconds, and the asphalt material cannot be fully modified. Moreover, the asphalt material is an organic material, while the basalt fiber is an inorganic material, which causes the asphalt material modified with the basalt fiber to be easily delaminated after being damaged by rain, resulting in the inability to effectively improve the performance of the asphalt material.
[0005] In order to increase the bonding effect between basalt fiber and asphalt material, and effectively improve the performance of asphalt material and extend its service life, the present invention provides a basalt fiber modification method, modified basalt fiber and application thereof. Summary of the invention
[0006] In order to solve the above-mentioned deficiencies in the prior art, increase the bonding effect between basalt fiber and asphalt material, and effectively improve the performance of asphalt material and extend its service life, the present invention provides a basalt fiber modification method, modified basalt fiber and application thereof.
[0007] The basalt fiber modification method, modified basalt fiber and application thereof of the present invention are achieved through the following technical solutions:
[0008] The first object of the present invention is to provide a method for modifying basalt fiber, comprising the following steps:
[0009] Step 1, after screening and removing impurities from basalt and drying, crushing to 5-10 mm to obtain basalt particles; then, mixing the basalt particles and oxide particles by ball milling to obtain a mixed powder;
[0010] Wherein, the oxide particles are a mixture of silicon dioxide and sodium oxide;
[0011] Step 2, smelting the mixed powder at 1250-1350° C. until it is completely melted to obtain a mixed melt; and drawing the mixed melt through a platinum-rhodium alloy bushing to obtain a fiber precursor;
[0012] Step 3, uniformly dispersing zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide and ethylenediamine in an alcohol solvent, and then performing a hydrothermal reaction at 160-180° C. to obtain a zinc oxide precursor solution;
[0013] Step 4, immersing the fiber precursor in the zinc oxide precursor solution, and performing a hydrothermal reaction at 200-230° C., thereby modifying the basalt fiber and obtaining the modified basalt fiber.
[0014] Furthermore, the mass ratio of the oxide particles to the basalt particles is 0.1 to 1:10.
[0015] Furthermore, in the oxide particles, the mass ratio of silicon dioxide to sodium oxide is 0.3 to 0.5:1.
[0016] Furthermore, the ball-to-material ratio of the ball milling treatment is 1:3, the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
[0017] Furthermore, the stirring treatment temperature is 40-60° C., and the stirring time is 14-20 hours.
[0018] Further, the zinc salt is zinc acetate;
[0019] The alcohol solvent is ethanol.
[0020] Furthermore, the usage ratio of the zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide, ethylenediamine and alcohol solvent is 1g:1.5-1.8g:0.5-0.8g:0.05mL:30-50mL.
[0021] Furthermore, in step 3, the hydrothermal reaction time is 6 to 12 hours;
[0022] In step 4, the hydrothermal reaction time is 16 to 30 hours.
[0023] Furthermore, the usage ratio of the fiber precursor to the zinc oxide precursor solution is 0.5-1g:1L.
[0024] Furthermore, the temperature of the drying treatment is 100-120° C., and the drying time is 16-20 hours.
[0025] The second object of the present invention is to provide a modified basalt fiber obtained by the above modification method.
[0026] The third object of the present invention is to provide an application of the modified basalt fiber in asphalt modifier.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention first removes impurities from basalt ore, dries and crushes it to obtain basalt particles, and then mixes the basalt particles and oxide particles evenly through ball milling. After the sodium oxide modifies the basalt, it helps to transform the crystalline structure of the basalt into an amorphous structure, thereby improving the flowability of the powder, and making it easier to quickly and evenly disperse it in the asphalt material when it is used as an asphalt modifier. The silicon dioxide can be dissolved in the alkaline solvent of the calcium hydroxide solution during the hydrothermal reaction process, so that the modified basalt fiber obtained forms a porous structure.
[0029] The present invention uniformly disperses zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide and ethylenediamine in an alcohol solvent, and then performs a hydrothermal reaction at 160-180°C. The obtained product contains not only a precursor of nano zinc oxide but also unreacted sodium hydroxide. Then, the fiber precursor obtained by drawing through a platinum-rhodium alloy plate is placed in the zinc oxide precursor solution. During the hydrothermal reaction, due to the presence of alkaline substances such as sodium hydroxide in the zinc oxide precursor solution, oxides such as silicon dioxide in the fiber precursor are dissolved in the solution system, thereby forming a porous structure in the obtained modified basalt fiber. At the same time, the presence of the nano zinc oxide precursor in the zinc oxide precursor solution forms nano zinc oxide during the hydrothermal process, thereby obtaining a modified basalt fiber with a porous structure composited with nano zinc oxide on the surface.
[0030] After the modified basalt fiber of the present invention is used for modified asphalt materials, the nano zinc oxide composited on the surface of the modified basalt fiber can not only effectively improve the anti-ultraviolet aging performance of the asphalt, but also increase the total surface free energy of the asphalt material, so that the asphalt mixture components are mixed more evenly, and can reduce the acid-base ratio of SFE in the asphalt binder, thereby improving the adhesion between the asphalt binder and the acidic aggregate that is easily damaged by moisture, thereby avoiding the occurrence of stratification of the asphalt mixture after being damaged by water.
[0031] The modification method of the present invention is simple to operate, and can preferably improve the fluidity of basalt fiber, can improve the bonding effect between basalt fiber and asphalt material, achieve improvement of the performance of asphalt material, and further extend the service life of asphalt material, which is conducive to promotion and large-scale production. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0033] The present invention provides a method for modifying basalt fiber, comprising the following steps:
[0034] Step 1, screening and removing impurities from basalt, drying and then crushing to obtain basalt particles; then, mixing the basalt particles and oxide particles by ball milling to obtain a mixed powder;
[0035] It should be noted that the present invention adopts the screening method commonly used in the art to remove impurities in basalt, so as to remove other impurities and improve the purity of basalt. And the present invention does not limit the specific process parameters of the drying treatment, as long as part of the water in the basalt is removed to facilitate subsequent crushing into particles. Preferably, the drying temperature of the present invention is 100-120°C and the drying time is 16-20h. And in order to facilitate the modification of basalt particles, the present invention preferably crushes them to 5-10mm.
[0036] It should be noted that the present invention preferably uses a mixture of silicon dioxide and sodium oxide as oxide particles to modify the basalt particles. After the oxide particles and basalt particles are mixed, during the ball milling process, the sodium oxide in the basalt modifies the basalt, which helps to transform the crystalline structure of the basalt into an amorphous structure, improve the flow properties of the powder, and then facilitate it to be used as an asphalt modifier. Quickly and evenly dispersed in the asphalt material; the silicon dioxide in the hydrothermal reaction process can be dissolved in the alkaline solvent of the calcium hydroxide solution, and the obtained modified basalt fiber forms a porous structure. And in order to ensure the above-mentioned modification effect, the present invention preferably uses a mixture of silicon dioxide and sodium oxide in a mass ratio of 0.3 to 0.5:1 as oxide particles, and the particle size of the oxide particles is 0.1 to 1 mm. The oxide particles and basalt particles are mixed in a mass ratio of 0.1 to 1:10 and ball milled.
[0037] In order to ensure that the basalt particles and the oxide particles are fully modified during the ball milling process, the preferred ball-to-material ratio of the ball milling treatment is 1:2-4, the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
[0038] Step 2, smelting the mixed powder at 1250-1350° C. until it is completely melted to obtain a mixed melt; and drawing the mixed melt through a platinum-rhodium alloy bushing to obtain a fiber precursor;
[0039] It should be noted that the present invention uses a platinum-rhodium alloy wire drawing method after melting the basalt particles modified by oxide particles to make a fiber precursor. The principle is the same as that of the prior art, so it will not be repeated here.
[0040] Step 3, uniformly dispersing zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide and ethylenediamine in an alcohol solvent, and then performing a hydrothermal reaction at 160-180° C. to obtain a zinc oxide precursor solution;
[0041] It should be noted that zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide and ethylenediamine are uniformly dispersed in an alcohol solvent and subjected to a hydrothermal reaction to obtain a solution system containing not only the precursor of nano zinc oxide but also unreacted sodium hydroxide.
[0042] In order to ensure the content of nano zinc oxide precursor in the zinc oxide precursor solution so that a layer of nano zinc oxide can be evenly coated on the surface of the fiber precursor in the subsequent hydrothermal process, the present invention preferably uses zinc acetate as the zinc salt and ethanol as the alcohol solvent, and the dosage ratio of zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide, ethylenediamine and alcohol solvent is 1g:1.5-1.8g:0.5-0.8g:0.05mL:30-50mL.
[0043] Step 4, immersing the fiber precursor in the zinc oxide precursor solution, and performing a hydrothermal reaction at 200-230° C., thereby modifying the basalt fiber and obtaining modified basalt fiber;
[0044] It should be noted that the zinc oxide precursor solution of the present invention is a mixture of a zinc oxide precursor solution of nano zinc oxide and an unreacted sodium hydroxide solution. When the fiber precursor is immersed in the zinc oxide precursor solution, during the hydrothermal reaction, due to the presence of alkaline substances such as calcium hydroxide in the zinc oxide precursor solution, oxides such as silicon dioxide in the fiber precursor are dissolved in the solution, thereby forming a porous structure of the obtained modified basalt fiber; at the same time, the presence of the nano zinc oxide precursor in the zinc oxide precursor solution forms nano zinc oxide during the hydrothermal process, thereby obtaining a modified basalt fiber with a porous structure composited with nano zinc oxide on the surface. And preferably, the amount ratio of the fiber precursor to the zinc oxide precursor solution is 0.5 to 1 g: 1L.
[0045] Example 1
[0046] This embodiment provides a modified basalt fiber, which is prepared by the following steps:
[0047] 1) The basalt is screened to remove impurities, then placed in an oven at 110° C. for 18 hours for drying, taken out and cooled to room temperature, and then crushed to 5-10 mm by a crusher to obtain basalt particles.
[0048] 2) Silicon dioxide and sodium oxide were mixed at a mass ratio of 0.4:1 to obtain oxide particles; then, 1 kg of the basalt particles obtained above were taken, mixed with the oxide particles at a mass ratio of 10:0.5, placed in a high-energy ball mill, the ball-to-material ratio was set to 1:3, and ball milled at a ball milling speed of 300 r / min for 8 hours to obtain a mixed powder.
[0049] 3) The mixed powder obtained above is smelted at 1300° C. until it is completely melted, and then drawn through a platinum-rhodium alloy plate to obtain a fiber precursor.
[0050] 4) Zinc acetate, hexadecyltrimethylammonium bromide, sodium hydroxide, ethylenediamine and ethanol were uniformly mixed in a dosage ratio of 1 g:1.7 g:0.6 g:0.05 mL:50 mL, and then hydrothermally reacted at 170° C. for 7 h to obtain a zinc oxide precursor solution.
[0051] 5) The fiber precursor prepared in the above step 3) is mixed with the above zinc oxide precursor solution at a dosage ratio of 0.7g:1L, and then a hydrothermal reaction is carried out at 220°C for 18h to achieve the modification of the basalt fiber and obtain modified basalt fiber.
[0052] Example 2
[0053] This embodiment provides a modified basalt fiber, and the preparation method thereof is different from that of embodiment 1 only in that:
[0054] In this embodiment, the drying temperature is 100°C and the drying time is 16 hours;
[0055] The mass ratio of the oxide particles to the basalt particles is 0.1:10, and the mass ratio of silicon dioxide to sodium oxide in the oxide particles is 0.3:1;
[0056] The ball-to-material ratio of the ball milling treatment is 1:2, the ball milling speed is 200r / min, and the ball milling time is 4h;
[0057] The zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide, ethylenediamine and alcohol solvent are used in a ratio of 1 g: 1.5 g: 0.5 g: 0.05 mL: 30 mL;
[0058] In step 4), the hydrothermal reaction time is 6 hours;
[0059] In step 5), the hydrothermal reaction time is 16 hours.
[0060] Example 3
[0061] This embodiment provides a modified basalt fiber, and the preparation method thereof is different from that of embodiment 1 only in that:
[0062] In this embodiment, the drying temperature is 120°C and the drying time is 20h;
[0063] The mass ratio of the oxide particles to the basalt particles is 1:10, and the mass ratio of silicon dioxide to sodium oxide in the oxide particles is 0.5:1;
[0064] The ball-to-material ratio of the ball milling treatment is 1:4, the ball milling speed is 400r / min, and the ball milling time is 12h;
[0065] The zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide, ethylenediamine and alcohol solvent are used in a ratio of 1 g:1.8 g:0.8 g:0.05 mL:50 mL;
[0066] In step 4), the hydrothermal reaction time is 6 to 12 hours;
[0067] In step 5), the hydrothermal reaction time is 16 to 30 hours.
[0068] Example 4
[0069] This embodiment provides a modified basalt fiber asphalt material, and the preparation method thereof is as follows:
[0070] After the modified basalt fiber obtained in Example 1 is made into chopped fibers, the obtained chopped fibers are evenly mixed with asphalt at a mass ratio of 1:100 to obtain a modified basalt fiber asphalt material.
[0071] Example 5
[0072] This embodiment provides a modified basalt fiber asphalt material, and the preparation method thereof is different from that of embodiment 4 only in that:
[0073] The modified basalt fiber obtained in Example 2 was made into chopped fibers.
[0074] Example 6
[0075] This embodiment provides a modified basalt fiber asphalt material, and the preparation method thereof is different from that of embodiment 4 only in that:
[0076] The modified basalt fiber obtained in Example 3 was made into chopped fibers.
[0077] Comparative Example 1
[0078] This comparative example provides a modified basalt fiber, and the preparation method thereof is different from that of Example 1 only in that:
[0079] In this comparative example, no oxide particles were added.
[0080] Comparative Example 2
[0081] This comparative example provides a modified basalt fiber, and the preparation method thereof is different from that of Example 1 only in that:
[0082] In this comparative example, only sodium oxide was used as oxide particles.
[0083] Comparative Example 3
[0084] This comparative example provides a modified basalt fiber, and the preparation method thereof is different from that of Example 1 only in that:
[0085] Steps 5 and 6, the step of compounding nano zinc oxide on the fiber surface, are not performed.
[0086] Experimental Section
[0087] (I) Structural performance test of basalt fiber
[0088] The present invention takes the modified basalt fibers of Examples 1-3 and Comparative Examples 1-2 as examples, and tests their structural properties respectively. The test results are shown in Table 1.
[0089] Table 1 Structural properties of basalt fiber
[0090] <![CDATA[Density g / cm 3 > Porosity % Diameter μm Example 1 0.7 81 65~75 Example 2 1.0 60 55~64 Example 3 1.4 52 45~54 Comparative Example 1 3.1 0.03% 35~44 Comparative Example 2 3.0 0.1% 35~44 Comparative Example 3 2.4 20 50~70
[0091] As shown in Table 1, by comparing the structural properties of Example 1 and Comparative Examples 1-3, it can be seen that the modified basalt fiber prepared by the present invention has a low density and a high porosity, and has a porous structure, indicating that the components of the oxide particles and whether they are added or not play a very important role in the structure of the basalt fiber, and whether the nano zinc oxide is coated or not also has an important influence on its structure. And from the structural properties of Examples 1-3, it can be seen that the parameters of each step have an influence on its structural properties, indicating that the improvement of the basalt fiber material structure achieved by the present invention is not based on a single component or processing step, but is achieved through the synergistic effect of each component and each step being carried out in sequence.
[0092] (II) Performance test of modified asphalt materials
[0093] The present invention takes the modified asphalt materials of Examples 4-6 as examples, and tests the performances before and after aging, respectively. The test results are shown in Table 2.
[0094] The aging test was conducted in a rotary film oven, and the conditions of the aging test were: aging temperature 163°C, and ultraviolet light irradiation 48 hours.
[0095] Table 2 Performance test results of modified asphalt materials
[0096] Example 4 Example 5 Example 6 5℃ elongation (5cm / min) 34.5 30.3 31.4 25℃ elastic recovery (%) 100 100 99 Needle penetration 25℃(100g,5s,0.1mm) 51.1 45.5 48.6 135℃ Kinematic viscosity (Pa.s) 1.3 0.9 1.0 Water permeability coefficient (mL / min) 0 0 0 Aging 5℃ Elongation (5cm / min) 28.1 21.2 22.3 Aging 25℃ Elastic recovery (%) 92.0 91.0 89.8 Aging penetration 25℃(100g,5s,0.1mm) 36.8 32.1 34.4
[0097] It can be seen from Table 2 that after the modified basalt fiber of the present invention is used to prepare the modified asphalt material, the modified asphalt material has excellent mechanical properties. And by comparing the performance data before and after aging, it can be seen that the performance of the present invention after aging is not much different from that before aging, indicating that the modified basalt fiber prepared by the present invention can be used in the modified asphalt material to effectively improve the anti-ultraviolet aging performance of asphalt and delay the aging of asphalt materials.
[0098] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for modifying basalt fiber, characterized in that: The following steps are involved: Step 1, after screening and removing impurities from basalt and drying, crushing to 5-10 mm to obtain basalt particles; Subsequently, the basalt particles and the oxide particles are mixed uniformly by ball milling to obtain a mixed powder; Wherein, the oxide particles are a mixture of silicon dioxide and sodium oxide; Step 2, smelting the mixed powder at 1250-1350° C. until it is completely melted to obtain a mixed melt; and drawing the mixed melt through a platinum-rhodium alloy bushing to obtain a fiber precursor; Step 3, uniformly dispersing zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide and ethylenediamine in an alcohol solvent, and then performing a hydrothermal reaction at 160-180° C. to obtain a zinc oxide precursor solution; Step 4, immersing the fiber precursor in the zinc oxide precursor solution, and performing a hydrothermal reaction at 200-230° C., thereby modifying the basalt fiber and obtaining modified basalt fiber; The mass ratio of the oxide particles to the basalt particles is 0.1 to 1:10; In the oxide particles, the mass ratio of silicon dioxide to sodium oxide is 0.3 to 0.5:1; The dosage ratio of the zinc salt, hexadecyltrimethylammonium bromide, sodium hydroxide, ethylenediamine and alcohol solvent is 1g:1.5-1.8g:0.5-0.8g:0.05mL:30-50mL; In step 3, the hydrothermal reaction time is 5 to 10 hours; In step 4, the hydrothermal reaction time is 16 to 30 hours; The dosage ratio of the fiber precursor to the zinc oxide precursor solution is 0.5-1g:1L.
2. The modification method according to claim 1, characterized in that The ball-to-material ratio of the ball milling treatment is 1:2-4, the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
3. The modification method according to claim 1, characterized in that: The zinc salt is zinc acetate; The alcohol solvent is ethanol.
4. A modified basalt fiber obtained by the modification method according to any one of claims 1 to 3.
5. Use of the modified basalt fiber according to claim 4 in an asphalt modifier.
